Identification and characterization of arthropod damage on Dioscorea in Montes de María, Colombia: arthropods in yams - Pérez Cantero, Shirley Patricia (2022)
Since the development of agriculture, crops have been prone to attack by various pests, which reduce yields and productivity. Therefore, it is essential to know the biology and behavior of arthropod pests in order to establish integrated management plans to reduce damage and maximize food production to meet the food demand of a growing population. In the Montes de María sub-region of Colombia, pest damage has been reported in recent years, but their taxonomic identity, incidence and damage capacity are unknown. In this sense, Agrosavia C.I Turipaná developed an investigation to identify and characterize the damage caused by arthropod pests on Dioscorea alata and D. rotundata in the municipalities of Carmen de Bolívar (Bolívar) and Chalán (Sucre) during the vegetative stage. Arthropod monitoring was carried out every two weeks and in each sampling the damage and arthropods found on leaves and stems of the plant were recorded. The results showed that in both locations and yam species the leaves of the plant were affected by five arthropod pests of the order Coleoptera (family Chrysomelidae) and three Hemiptera of the family Cicadellidae and Miridae. The damage found on the stem was associated with Xystus sp. Arthropod pest evaluations on yam species constitute a promising strategy for the prevention of health risks in the crop, which will contribute to the eco-efficient production of yam tubers.